Boin, Arjen, Paul ‘t Hart, Eric Stern y Bengt Sundelius (2017), The Politics of Crisis Management: Public Leadership Under Pressure, Cambridge, Cambridge University Press, 206 pp. - García Pacheco, José Angel (Gestión y Política Pública, 2020)
Reseña del libro The Politics of Crisis Management: Public Leadership Under Pressure de Arjen Boin, Paul ‘t Hart, Eric Stern y Bengt Sundelius.